LAND CONVERSION PROCESSES AND LOCAL COMMUNITY ASSESSMENT IN THE DISTRICT OF PETALING - Zainudin, Liyana; Mohd Yusoff, Zaharah; Sulaiman, Saiful Aman; Abu, Jaiya (PLANNING MALAYSIA, 2021)
Land use planning is part and parcel of both land development and town planning. In Malaysia, these two areas are steered independently, the former by a state or district’s land office and the latter by the state’s local authority. This study looks at the aspects of land development where land use conversion plays a crucial part, where it brings significance to land revenue. As the leading district in Malaysia, the district of Petaling is undeniably the busiest land office in the nation, working hand-in-hand with three city councils. Land premium that is imposed on approved applications for land use conversion has been one of the main contributors to the district and state’s revenue as a whole. Given the hefty charges that have been imposed by the consultants for land use conversions, it is found that the application charges that are imposed by the land office are minimal. An assessment study on land conversion has been conducted and the result shows that the local community assessment score on familiarity, collectively stands at only 40%. It is recommended that an awareness on land use as basic knowledge should be given priority as it may contribute to more efficient land development and town planning, as a whole.